(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In order to pass emergency vehicles without incident, this study proposes an intelligent traffic management system. It is difficult to remove or destroy the unique radio frequency identification (RFID) tag that is attached to every single vehicle and is strategically positioned. To read the RFID tags affixed to the car, we utilise an RFID reader, NSK EDK-125-TTL, and PIC16F877A system-on-chip. It keeps track of the number of cars that go along a certain road during a given period of time. Additionally, it establishes network congestion and, therefore, the length of the green light for that route. If the RFID tag is from a stolen car, a message is delivered to the police control centre via GSM SIM300. Additionally, an ambulance will signal the traffic controller at the intersection to switch on the green light as it approaches the intersection. The ambulance and traffic controller may communicate wirelessly with one another because to this module’s utilisation of ZigBee modules on the CC2500 and the PIC16F877A system-on-chip. The prototype was put to the test in our wireless communication lab using a variety of input combinations, and the experimental outcomes were as anticipated.